Comparison of access to services in rural emergency departments in Quebec and British Columbia. Issue 6 (November 2014) - Fleet, Richard; Audette, Louis-David; Marcoux, Jérémie; Villa, Julie; Archambault, Patrick; Poitras, Julien
ABSTRACT: Introduction: Although emergency departments (EDs) in Canada's rural areas serve approximately 20% of the population, a serious problem in access to health care services has emerged. Objective: The objective of this project was to compare access to support services in rural EDs between British Columbia and Quebec. Methods: Rural EDs were identified through the Canadian Healthcare Association's Guide to Canadian Healthcare Facilities. We selected hospitals with 24/7 ED physician coverage and hospitalization beds that were located in rural communities (using the rural and small town definition from Statistics Canada). Data were collected from ministries of health, local health authorities, and ED statistics. A telephone interview was administered to collect denominative user data statistics and determine the status of services. Results: British Columbia has more rural EDs (n 5 34) than Quebec (n 5 26). EDs in Quebec have higher volumes (19, 310 versus 7, 793 annual visits). With respect to support services, 81% of Quebec rural EDs have a 24/7 on-call general surgeon compared to 12% for British Columbia. Nearly 75% of Quebec rural EDs have 24/7 access to computed tomography versus only 3% for British Columbia. Rural EDs in Quebec are also supported by a greater proportion of intensive care units (88% versus 15%); however, British Columbia appears to have more medevac aircraft/helicopters than Quebec. Conclusions: The results suggest that major differences exist in access to support services in rural EDs in British Columbia and Quebec. A nationwide study is justified to address this issue of variability in rural and remote health service delivery and its impact on interfacility transfers and patient outcomes.